2017
DOI: 10.1039/c7sm00983f
|View full text |Cite
|
Sign up to set email alerts
|

Lattice symmetries and the topologically protected transport of colloidal particles

Abstract: The topologically protected transport of colloidal particles on top of periodic magnetic patterns is studied experimentally, theoretically, and with computer simulations. To uncover the interplay between topology and symmetry we use patterns of all possible two dimensional magnetic point group symmetries with equal lengths lattice vectors. Transport of colloids is achieved by modulating the potential with external, homogeneous but time dependent magnetic fields. The modulation loops can be classified into topo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 57 publications
2
52
0
Order By: Relevance
“…Patterned magnetic substrates, while limited in their reconfigurability, are a promising system for microfludic transport, as they allow for particle transport at quite high velocities [35]. Recent work with these substrates has demonstrated that, due underlying to lattice symmetries, certain transport paths are topologically protected [38,39]. This system has also been used to create a landscape with quenched disorder by permanently placing large obstacles at random positions on the substrate, and then studying their interaction with translating magnetic particles [40].…”
Section: Substrate Based-drivingmentioning
confidence: 99%
“…Patterned magnetic substrates, while limited in their reconfigurability, are a promising system for microfludic transport, as they allow for particle transport at quite high velocities [35]. Recent work with these substrates has demonstrated that, due underlying to lattice symmetries, certain transport paths are topologically protected [38,39]. This system has also been used to create a landscape with quenched disorder by permanently placing large obstacles at random positions on the substrate, and then studying their interaction with translating magnetic particles [40].…”
Section: Substrate Based-drivingmentioning
confidence: 99%
“…where H ext (t) is the external field at time t and H p (x A ) is the magnetic field created by the pattern at position of the particle x A in action space A, see Refs. [22,23]. The particles interact via the purely repulsive Weeks-Chandler-Andersen potential where r is the distance between the particles, fix our unit and energy, and σ is the effective particle length that we fix to σ/a = 0.2 which is the same as in the experiments (transport of single spheres).…”
Section: Multi Particle Transportmentioning
confidence: 99%
“…Its possible use in creating magnetic logic elements has similarly been proven [14] as its potential to create engineered domain patterns by ion beam writing or when combined with lithographical techniques [1,4,[15][16][17]. The latter patterns have shown to be useful for magnetic particle transport by moving domain walls [18], by changing potential energy landscapes associated with the stray fields above the engineered domains [19,20] or by topological transport [21].…”
Section: Introductionmentioning
confidence: 99%